Beyond humanization and de-immunization: tolerization as a method for reducing the immunogenicity of biologics. Issue 6 (November 2013) - De Groot, Anne S; Terry, Frances; Cousens, Leslie; Martin, William
Immune responses to some monoclonal antibodies (mAbs) and biologic proteins interfere with their efficacy due to the development of anti-drug antibodies (ADA). In the case of mAbs, most ADA target 'foreign' sequences present in the complementarity determining regions (CDRs). Humanization of the mAb sequence is one approach that has been used to render biologics less foreign to the human immune system. However, fully human mAbs can also drive immunogenicity. De-immunization (removing epitopes) has been used to reduce biologic protein immunogenicity. Here, we discuss a third approach to reducing the immunogenicity of biologics: introduction of Treg epitopes that stimulate Treg function and induce tolerance to the biologic protein. Supplementing humanization (replacing xeno-sequences with human) and de-immunization (reducing T effector epitopes) with tolerization (introducing Treg epitopes) where feasible, as a means of improving biologics 'quality by design', may lead to the development of ever more clinically effective, but less immunogenic, biologics.